Young people who are being bullied – do they want general practice support?. Issue 1 (December 2016) - Scott, Emma; Dale, Jeremy; Russell, Rachel; Wolke, Dieter
Abstract Background Childhood bullying is a major risk factor for health, education and social relationships, with effects persisting into adulthood. It affects half of all children at some point, with 10–14 % experiencing bullying that lasts for years. With the advent of cyberbullying, it can happen at all times and places. There have been calls for GPs to take a more active role in identifying and supporting young people who are being bullied. This paper explores young people's and parents' opinions about whether general practice should be involved in identifying and supporting young people who are being bullied. Methods Two hundred six young people (85.9 % female, mean ± sd age 16.2 ± 3.2 years) and 44 parents were recruited through established bullying charity websites and their social media channels to complete an online questionnaire comprising multiple-choice questions and unlimited narrative responses. Questionnaire responses were analysed by age and gender using descriptive statistics. A descriptive analysis of the narrative responses was undertaken and key themes identified. Results Young people (90.8 %) and parents (88.7 %) thought it was important for GPs to be better able to recognise and help young people who are being bullied. Most recognised the link between bullying and health. The doctor's independence was seen as advantageous. Young people preferred completing a screening questionnaire to disclose experience of being bullied than being asked directly. They expressed concerns about how questions would be asked and whether information would be shared with parents/guardians. Parents were supportive of the use of a screening questionnaire, and most expected their child's disclosure to be shared with them. Conclusion Young people and parents recruited through anti-bullying websites and social media would welcome greater GP involvement in identifying and supporting young people who are being bullied and their families, provided it is offered in a caring, compassionate and confidential manner.